USING COMPUTER TECHNOLOGY IN INTERSUBJECT PROJECTS OF PHYSICS DURING THE STUDY PRACTICE - Guy, H.O. (Journal of Information Technologies in Education (ITE), 2010)
This article discusses the use of computer technology in the performance of students in physics interdisciplinary projects during the academic practice.